2018
DOI: 10.1021/acs.analchem.8b01703
|View full text |Cite
|
Sign up to set email alerts
|

Identification of YTH Domain-Containing Proteins as the Readers for N1-Methyladenosine in RNA

Abstract: N1-methyladenosine (mA) is an important post-transcriptional modification in RNA; however, the exact biological role of mA remains to be determined. By employing a quantitative proteomics method, we identified multiple putative protein readers of mA in RNA, including several YTH domain family proteins. We showed that YTHDF1-3 and YTHDC1, but not YTHDC2, could bind directly to mA in RNA. We also found that Trp in YTHDF2, a conserved residue in the hydrophobic pocket of the YTH domain that is necessary for its b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
194
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(202 citation statements)
references
References 26 publications
8
194
0
Order By: Relevance
“…6A and SI Appendix, Fig. S8H) as described previously (32). Fluorescence microscopy showed that the replication of VSV GFP was inhibited by siFOXO3 in peritoneal macrophages from Ifnar1 +/+ mice but not in Ifnar1 −/− peritoneal macrophages (Fig.…”
Section: Foxo3 Is Pivotal In Ythdf3-mediated Negative Regulation Of Asupporting
confidence: 65%
See 1 more Smart Citation
“…6A and SI Appendix, Fig. S8H) as described previously (32). Fluorescence microscopy showed that the replication of VSV GFP was inhibited by siFOXO3 in peritoneal macrophages from Ifnar1 +/+ mice but not in Ifnar1 −/− peritoneal macrophages (Fig.…”
Section: Foxo3 Is Pivotal In Ythdf3-mediated Negative Regulation Of Asupporting
confidence: 65%
“…However, the other m 6 A methyltransferases may influence the function of YTHDF3. An alternative mechanism was suggested by a recent report showing that YTHDF1-3 and YTHDC1 could bind directly also to N 1 -methyladenosine-(m 1 A-) modified RNAs (32). W432 in YTHDF2, which is a conserved residue similar to W438 in YTHDF3, was also required for its recognition of m 1 A.…”
Section: Foxo3 Is Pivotal In Ythdf3-mediated Negative Regulation Of Amentioning
confidence: 99%
“…Immunoprecipitation, pull‐down, mass‐spectrometry, and RNA‐seq approaches have begun to identify proteins whose interactions with mRNAs are mediated by modifications. These studies reveal that m 6 A, m 1 A, and m 5 C are specifically recognized by proteins that can either read or erase modifications to alter mRNA translation, localization, and stabilization (reviewed in X. Dai et al, ; X. Li et al, ; F. Liu et al, ; Peer et al, ; Roundtree, Evans, et al, ; S. Schwartz, ; Trixl & Lusser, ; Yang et al, ). To date, no “readers” or “erasers” of other mRNA modifications have been reported, though it has been proposed that the ribosome can serve as a universal reader of modifications in mRNA coding regions (Gilbert, Bell, & Schaening, 2016).…”
Section: Current Quantitative Perspective On Mrna Modificationsmentioning
confidence: 99%
“…Similar to m6A, installing a methyl group at the N1 position of adenosine forms N1-methyladenosine (m1A). Nine members of m1A regulators have been identified till now including writers (TRMT6, TRMT61A, TRMT10C), readers (YTHDF1, YTHDC1) and erasers (ALKBH1, ALKBH3) [5,92,93]. Dysregulation of m1A components was found to promote the progression of gastric cancer and bladder cancer via activation of several oncogenic pathways such as PI3K/AKT/mTOR and ErbB Pathways [94].…”
Section: N1-methyladenosine (M1a) 5-methylcytidine (M5c) and Pseudoumentioning
confidence: 99%